Rama or ahimsa? Terror or Passive Resistance? Revolutionary Methods of Hindu Students from London University and the Christian Response, 1909–17. (2015) - Mews, Stuart
Abstract : The assassination in London on the evening of 1 July 1909 of Sir Curzon Wyllie, aide-de-camp to the Secretary of State for India, by a twenty-six-year-old Indian student named Madar Lai Dhingra stunned the nation. The background to the shooting and its consequences shed light on the attitudes of British Christians to Indian Hindus. In turn light is shed on the response of Hindus, most crucially that of the eventual leader of the successful campaign for Indian independence, Mohandas Karamchand Gandhi, in the crucial decade before the First World War.